Revision of global carbon fluxes based on a reassessment of oceanic and riverine carbon transport - Resplandy, L; Keeling, R; Rödenbeck, C; Stephens, B; Khatiwala, S; Rodgers, K; Long, M; Bopp, L; Tans, P (Springer Nature, 2018)
Measurements of atmospheric CO2 concentration provide tight constraints on the sum of the land and ocean sinks. This constraint has been combined with estimates of the ocean carbon flux and the riverine transport of carbon from land to oceans to isolate the land sink. Uncertainties in the ocean and river fluxes therefore translate into uncertainties in the land sink. Here, we introduce a heat-based constraint on the latitudinal distribution of ocean and river carbon fluxes, and reassess the partition between ocean, river and land in the tropics, and in the southern and northern extra-tropics. We show that the ocean overturning circulation and biological pump tightly link the ocean transports of heat and carbon between hemispheres. Using this coupling between heat and carbon, we derive ocean and river carbon fluxes compatible with observational constraints on heat transport. This heat-based constraint requires a 20% to 100% stronger ocean and river carbon transport from the Northern Hemisphere to the Southern Hemisphere than existing estimates, and supports an upward revision of the global riverine carbon flux from 0.45 to 0.78 PgC/y. These systematic biases in existing ocean/river carbon fluxes redistribute up to 40% of the carbon sink between northern, tropical and southern land ecosystems. As a consequence, the magnitude of both the southern land source and the northern land sink may have to be substantially reduced.